Potential distribution of Batrachochytrium dendrobatidis in Argentina: implications in amphibian conservation - Ghirardi, Romina (2011)
Within the last two decades Batrachochytrium dendrobatidis (B.d.), the causative agent of chytridiomycosis, seems to have become a pandemic parasite, and is proposed as one of the more important causes of amphibian declines worldwide. In Argentina, the first report was in 2002 in Leptodactylus ocellatus. Since then, the fungus has expanded through different environments and species. In this study, we predict B.d. distribution in Argentina applying niche modelling based on reports of infected amphibians and environmental variables. The distribution hypothesis showed regions with highest suitability for B.d. including habitat types with (1) the most diverse amphibian fauna in Argentina such as the Parana River Basin, (2) endangered species, such as north Patagonia and northwest Andean highlands, and (3) wide range of optimum precipitation and temperatures allowing development of B.d..